ANALISIS IMPLEMENTASI STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL DALAM PERSPEKTIF TEORI INSTITUSIONAL: STUDI KASUS PADA PEMERINTAH KOTA MALANG - Wahyuni, Nina Eka (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research has a purpose to perform in depth observations on the implementation of Accrual Based Government Accounting Standards in Malang government reviewed in the perspective of institutional theory. The method used in this research process is qualitative descriptive Interpretive. The existence of the state of financial reform in Indonesia, particularly in the area of government accounting standards is one of New Public Management issued by the International agency with reference to the theories in the private sector. This is because the government considered as organizations that have low quality and do not provide clear accountability to the public. However, based on research results, the implementation of Accrual Based Government Accounting Standards in Pemerintah Kota Malang made possible by the existence of a rule attached to Regulation of Permendagri No. 64 Tahun 2013, which states that the implementation of Accrual Based Government Accounting Standards should be implemented at the latest by the year 2015. In other words, Pemerintah Kota Malang implement Accrual Based Government Accounting Standards due to a pressure from the organization that has more power, in this case the state called coercive isomorphism. This condition is an institutionalization process that occurs in a government organization. Given the human resources owned by the government do not have accounting background, then one recommendation that can be given is to give an in depth education on the meaning of accrual based government accounting standards. So, later on the implementation of the policy changes in government accounting basis this can be done well, namely in terms of meaning theoretically and financial statements are produced.Â Â Keywords: Accrual Based Government Accounting Standards, Institutional Theory, Pemerintah Kota Malang